Ars moriendi and the Senses - Leppin, Volker (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2025)
Late medieval artes moriendi are an example of the opposition between spiritual and bodily senses, as is otherwise known in mystical texts. The artes moriendi counselled believers in their hour of death, when their physical senses were fading away. As this article will argue, this handicap could turn into an advantage when it led to a focus on the spiritual senses. Seeing with the inner eye would bring believers onto the path to God and, thus, help them to overcome temporal death through eternal life. Even if the genre of ars moriendi came to an end with the Reformation in Protestant countries, the idea of spiritual senses overcoming death survived.